الاتساق المعجمي في القرآن الكريم: دراسة نصية تحليلية في سورة فاطر - حميدة دهنون; صفاء عيساوي (University of El-oued, 2025)
خص تناولت الدراسة موضوعاً مهماً في اللسانيات النصية تمثل في الاتساق المعجمي في القرآن الكريم كما تجلى في سورة فاطر من خلال العلاقات المعجمية القائمة بين العبارات النص من خلال عنصرين أساسيين هما التكرار والتضام (أو المصاحبة المعجمية). وفي أثناء ذلك كنا نجيب عن إشكالية عامة تمثل في السؤال عن حقيقة الاتساق المعجم وكيف تجلى بتكراره وتضامه في سورة فاطر وقد أسعفتنا سورة فاطر في خدمة هدفنا من الدلالة النصية لما توفرت عليه من وفرة وتنوع في عنصري التكرار والتضام المعجميين الموصلين إلى التماسك النصي في جانبه المعجمي Th This study addresses an important topic in text linguistics, namely lexical cohesion in the Holy Qur’an, as exemplified in Surah Fatir, through the lexical relations established between phrases in the text via two main elements: repetition and collocation (lexical association). The study seeks to answer a central research question: what is the nature of lexical cohesion, and how is it manifested through repetition and collocation in Surah Fatir? Surah Fatir proved particularly to be useful in serving the purpose of our textual-semantic analysis due to its richness and diversity in the use of both repetition and lexical collocation, which contributed significantly to the lexical aspect of textual cohesion
مذكرة .ماستر . لسانيات عامة. 2025
Keywords: لسانيات النص، الاتساق، التكرار، التضام، سورة فاطر; Text linguistics; cohesion; repetition; collocation; Surah Fatir